THE IMPACT OF FAMILY SUPPORT ON FEELINGS OF LONELINESS IN THE ELDERLY IN THE BLUE HOUSE OF BATUSANGKAR - Oktavia, Viola; desmita, desmita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Old age is the final stage of human life. The aging process is a lifelong process, not only starting from a certain time but starting from the beginning of human life. Older age is like the sun that is sinking, emitting an orange color that is full of meaning when footsteps become slower and hair turns white very quickly, this is a time when someone can enjoy the results of their sweat and hard work, but besides that, loneliness increasingly haunts them, ties Social issues are starting to weaken and the loss of a life partner is a contributing factor to this loneliness. Is it true that family support is a lamp that illuminates the darkness Therefore, researchers are very interested in the impact of family support on feelings of loneliness in the elderly in the Batusangkar blue house. The author used observation and interview methods to obtain results that family support has a very big impact in reducing feelings of loneliness. loneliness in the elderly. In the midst of life's long journey, a touch of affection, words of encouragement, and the physical presence of family members can provide calm.